Made in China: Crisis begets quality upgrade - Ruan, Jianqing; Zhang, Xiaobo (International Food Policy Research Institute, 2010)
The quality of manufactured products made in China has improved tremendously in the past several decades. In this paper, we argue that crises are instruments for the upgrade of Chinese manufactured goods. We first develop a theoretical framework to show that a crisis, if used wisely, could present good opportunities for entrepreneurs and local governments to form collective action to improve product quality. Next, we empirically test the hypothesis using a panel data set from 1990 to 2008 covering more than 100 clusters in the Zhejiang Province of China.